Technological and Analytical Methods for Arabinoxylan Quantification from Cereals. Issue 6 (25th April 2016) - Döring, Clemens; Jekle, Mario; Becker, Thomas
Abstract : Arabinoxylan (AX) is the major nonstarch polysaccharide contained in various types of grains. AX consists of a backbone of β1.4D-xylopyranosyl residues with randomly linked αl arabinofuranosyl units. Once isolated and included as food additive, AX affects foodstuff attributes and has positive effects on human health. AX can be classified into waterextractable and waterunextractable AX. For isolating AX out of their natural matrix, a range of methods was developed, adapted, and improved. This review presents a survey of the commonly used extraction methods for AX by the influence of different techniques. It also provides a brief overview of the structural and technological impact of AX as a dough additive. A concluding section summarizes different detection methods for analyzing and quantification AX.